Characterization of two protein disulphide iosmerases from the endocytic pathway of Trypanosoma brucei - NOLAN, DEREK (American Society for Biochemistry and Molecular Biology, 2005)
Proteins from the endocytic pathway in bloodstream forms of Trypanosome brucei are modified by the addition of linear poly-N-acetyllactosamine side chains, which permits their isolation by tomato lectin affinity chromatography. Antibodies against this tomato lectin binding fraction were employed to screen a cDNA expression library from bloodstream forms of T. brucei. Two cDNAs were prominent among those selected. These cDNAs coded for two putative protein disulfide isomerases (PDIs) that respectively contained one and two double-cysteine redox-active sites and corresponded to a single domain PDI and a class 1 PDI. Assays of the purified recombinant proteins demonstrated that both proteins possess isomerase activity, but only the single domain PDI had a reducing activity. These PDIs possess a number of unusual features that distinguish them from previously characterized PDIs. The expression of both is developmentally regulated, they both co-localize with markers of the endocytic pathway, and both are modified by N-glycosylation. The larger PDI possesses N-glycans containing poly-N-acetyllactosamine, a modification that is indicative of processing in the Golgi and suggests the presence of a novel trafficking pathway for PDIs in trypanosomes. Although generally PDIs are considered essential, neither activity appeared to be essential for the growth of trypanosomes, at least in vitro.
PUBLISHED
Keywords: Biochemistry